2021
DOI: 10.1039/d1na00382h
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Soxhlet extraction as a simple method for GO rinsing as a precursor of high-quality graphene

Abstract: Graphite-oxide (GO) is a valuable compound produced by the chemical oxidation of graphite. The procedure for converting graphite into GO includes two steps: oxidation and subsequent rinsing. Proper rinsing is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Traditional plant extraction methods include microwave-assisted extraction [ 12 ], air flow crushing extraction [ 13 ], Soxhlet extraction [ 14 ], etc. However, irradiating raw materials for an extended period of time with microwaves requires a lot of energy, and focused irradiation produces too much heat, which denaturizes flavonoids and other heat-sensitive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional plant extraction methods include microwave-assisted extraction [ 12 ], air flow crushing extraction [ 13 ], Soxhlet extraction [ 14 ], etc. However, irradiating raw materials for an extended period of time with microwaves requires a lot of energy, and focused irradiation produces too much heat, which denaturizes flavonoids and other heat-sensitive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…28–31 Further, the approximate number of rGO layers formed in both paper and cloth samples was calculated according to the literature. 32–34 It was observed that the minimum average number of rGO layers ( N = 11) was obtained on paper samples and the maximum average number of rGO layers ( N = 77) was found for cloth substrates, as shown in Section S4 (ESI†).…”
Section: Resultsmentioning
confidence: 92%
“…In this study, an ethanol extract of P. acidus (EEPA) leaves was made using a hot extraction method using a Soxhlet at a temperature of 70°C, because it is considered more effective for extracting secondary metabolites present in simplicia so that it can be extracted and produce a larger extract yield without destroying the secondary metabolites which contained in the plants. The extraction results obtained a thick extract with a dark green color with a distinctive odor with a yield of 12.12% [12]. The characteristics of P. acidus leaf were checking the ash content, water-soluble and ethanol-soluble extract content, as well as checking the water content to determine the specifications of the plant in question to meet the quality standards of an ingredient to become a standardized herbal medicine.…”
Section: The Results Of Extraction and Standardisation Of Eepamentioning
confidence: 99%